Asparaginase allergies: it’s all in the genes - Wetzler, Meir (American Society of Hematology, 2014)
In this issue of Blood, Fernandez et al demonstrate that human leukocyte antigen (HLA) DRB1 alleles confer high-affinity binding to asparaginase epitopes, leading to higher frequency of allergic reactions.(1) The authors initially examined HLA data from European ancestry patients enrolled onto St. Jude Children’s Research Hospital (n = 541) and the Children’s Oncology Group (n = 1329) clinical trials and identified a higher incidence of allergic reactions and anti-asparaginase antibodies in patients with HLA-DRB1*07:01 alleles. They then analyzed the structure of the HLA protein to show high-risk amino acids located within the binding pocket (see figure), possibly affecting the interaction between asparaginase epitopes and the HLA-DRB1 protein.